Multispecies Planning: Locating Nonhuman Entanglements in Oyster Restoration Policy on the Massachusetts Coast - Morgan, David. (Tufts University. Tisch Library., 2019)
Nature-based infrastructure (NBI) ties together ecology and planning. It is significant as an innovation and because it potentiates new and different human-environment relations. Drawing upon recent anthropological efforts to explore multispecies entanglements, this thesis considers the NBI work of the Massachusetts Oyster Project. It examines the ecological communities the organization joins in its efforts to restore the Eastern oyster, and it evaluates those relationships as indicators of potential shifts in state environmental policy. This thesis also elaborates multispecies planning as a concept. It incorporates evidence from ethnography, environmental science, philosophy, and political theory, and finds that the framework offers planners two lessons. First, it is now necessary to attend to many forms of knowledge in the planning process, not all of which are human. Second, entertaining such findings points to new ways of reasoning environmental matters of concern. Both lessons are given in the example of Massachusetts state shellfish policy.; Thesis (M.A.)--Tufts University, 2019.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Ann Rappaport.; Committee: Kristin Skrabut.; Keywords: Climate change, Cultural anthropology, and Public policy.